Hygiene and Sanitation in Rural Nepal: Progress and Ongoing Challenges - Lahare, Sabitra (Journal of Rapti Babai Campus, 2025)
This study delves into the current state of hygiene and sanitation in rural areas of Nepal, highlighting both the achievements and the ongoing hurdles faced by local communities. Through the concerted efforts of government initiatives and nongovernmental organizations, there has been visible progress in improving water supply, sanitation facilities, and basic hygiene practices. Despite the advances in infrastructure and community health awareness, rural Nepal still grapples with substantial barriers. Additionally, deeply rooted cultural practices sometimes restrict the adoption of modern sanitation techniques, further compounded by economic constraints that make it difficult for many households to invest in basic hygiene essentials. This article sheds light on the serious public health impacts arising from insufficient sanitation and hygiene measures. In communities where access to clean water and sanitary facilities remains a challenge, the prevalence of waterborne and communicable diseases is disproportionately high. To address these pressing concerns, this study proposes actionable solutions aimed at fostering sustainable hygiene and sanitation practices. In conclusion, while considerable strides have been made in improving hygiene and sanitation in rural Nepal, substantial work remains to ensure these benefits are sustainable and widely accessible. The findings of this study emphasize the critical need for ongoing support and funding, along with innovative strategies to overcome infrastructural, cultural, and economic barriers. Only with sustained commitment and community involvement can rural Nepal aspire to a future where all residents have the right to safe, clean, and healthy living conditions.